‘The Drunkard’s Raggit Wean’: Broadside Culture and the Politics of Temperance Verse - Kirstie Blair (Cahiers Victoriens et Edouardiens)
This article examines the circulation of a well-known temperance poem and song by Glasgow poet John Crawford, ‘The Drunkard’s Raggit Wean’, considering its function as a broadside and its reprinting in the newspaper press and other venues. It argues for the significance and continued popularity of broadsides in the mid-Victorian period, and highlights the importance of temperance verse in this period’s popular culture.